Fiscal Federalism and Income Inequality: An Empirical Analysis for Switzerland - Lars P. Feld; Christian Frey; Christoph A. Schaltegger; Lukas A. Schmid (Center for Economic Studies and ifo Institute (CESifo), 2018)
This paper analyzes the impact of fiscal federalism on income inequality and redistribution. Theoretically contradicting arguments ask for empirical evidence to obtain a better knowledge of this relationship. We rely on the institutional setting in Switzerland to study the issue empirically. According to our findings tax decentralization tends to reduce concentration in pre- and after-tax income without additional redistribution via progressive taxes. It is, however, crucial to consider the interdependence of decentralization and fragmentation as inequality decreasing effects of decentralization are counteracted by its interaction with fragmentation.
Keywords: D31; H23; H77; 330; federalism; decentralization; inequality; income concentration; top incomes; redistribution; Switzerland